A STUDY ON UNIVERSITY STUNDENTS’ PERCEPTION OF SERVICE QUALITY WITH SERVQUAL MEASUREMENT MODEL - Caglıyan, Vural; Genc, Asir; Yılmaz, Tarik (Fırat University, 2012)
Using SERVQUAL (SERVice QUALity) measurement model, this study aims to examine the relations between expectation and perception of university students at Department of Statistics, Faculty of Science Selçuk University with regard to quality of the services university offer to them. SERVQUAL measurement model is a method which is frequently used in literature to measure service quality and the validation of the scale used in this method have been determined in many previous studies. SERVQUAL measurement model and perception of service quality will be examined by Structural Equation Modeling (SEM) and the results will be compared to the results of the previous studies in literature. This study was also undertaken to lay basis for further studies which are going to carried out in different departments at Selçuk University. Key words: SERVQUAL Scale, Service Quality, Structural Equation Modeling